Analysis of Bullying Behavior in Elementary School Students in View of the Big Five Personality Types - Rahayu, Fitriani (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2024)
Bullying is an act of behavior accompanied by violence with intentional or unintentional actions by a group of people or individually, in which the violence is carried out physically or verbally. This research aims to determine students' bullying behavior using analysis of the Big Five personality types. This research is a type of descriptive qualitative research with a case study approach. Data was obtained using interview and observation techniques. The analysis in this research uses data reduction, data presentation and obtaining conclusions. The results of this study show that there are 3 types of bullying behavior that occur in elementary schools, namely physical bullying by hitting, verbal bullying by mocking and making fun of, calling friends by their parents' names, calling friends by funny names, saying rude things and insulting members. body. One of the causes of bullying behavior is personality type. Individuals with low agreeableness and conscientiousness personalities are said to have high levels of bullying behavior, while individuals with high levels of neuroticism or emotional stability are considered to have a tendency towards bullying behavior.